2021
DOI: 10.2147/ahmt.s292977
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Consultations: Young People and Their Parents’ Experience

Abstract: Purpose Evaluate the experience of virtual consultations for young people and their families and assess whether young people are being offered a confidential space as part of these virtual encounters. Patients and Methods An anonymous online survey was sent to young people age 10–18 y.o. who had experienced at least one virtual consultation with an adolescent medicine tertiary service in the United Kingdom between March 13th and June 13th 2020 mostly associated with, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…(38) However, there may have also been difficulties in accessing remote care due to lack of space to speak privately and insufficient phone data or internet connectivity to take video calls. (39) Access and utilization challenges disproportionately affect children and young people living in more deprived areas. (40) Reassuringly, we found the total contacts for primary care sensitive conditions such as urinary tract infections, appendicitis and epilepsy remained relatively high, and international reports confirm the incidence of these conditions changed little during this time.…”
Section: Discussionmentioning
confidence: 99%
“…(38) However, there may have also been difficulties in accessing remote care due to lack of space to speak privately and insufficient phone data or internet connectivity to take video calls. (39) Access and utilization challenges disproportionately affect children and young people living in more deprived areas. (40) Reassuringly, we found the total contacts for primary care sensitive conditions such as urinary tract infections, appendicitis and epilepsy remained relatively high, and international reports confirm the incidence of these conditions changed little during this time.…”
Section: Discussionmentioning
confidence: 99%
“…For patients, the benefits of remote consultations during the pandemic include continuity of care when face-to-face contact was not possible and reduced stress because it was not necessary to attend hospital. 23 However, previous research has found virtual consultations are effective for only a small fraction of patients who are considered ‘suitable’ for this type of care by clinicians, 24 and the effectiveness for adolescents, particularly those with SEN or receiving CSC services, is unclear. For example, virtual consultations may be more difficult for young people receiving CSC services due to a lack of required resources, such as digital devices and high-speed internet, which was an issue for this group during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond these revolutionary paths, digital progress is applied even to innovative approaches that are much more accessible. These take the form in eHealth, mobile-Health (mHealth) such as the telemedicine based on the obtained connectivity of mobile devices with the internet (74)(75)(76)(77). Today, given the current COVID-19 pandemic, several professional societies are encouraging the maximization of the use of telemedicine in current practice (78).…”
Section: Digital Innovationmentioning
confidence: 99%